Pengaruh Quality Of Work Life dan Kompetensi terhadap Career Plateau dengan Dimediasi Kepuasan Kerja (Studi Pada Pegawai Dinas Pendidikan Kota Semarang) - Pratama Alvian Pramana; Bambang Suko Priyono (STIE AMKOP, 2022)
Abstract The population in this study was the Semarang City Education Office Employees, which amounted to 95 Civil Servants (PNS). The sample in this study were employees of the Semarang City Education Office. Sampling by census sampling technique of 95 employees. Methods of data collection using a questionnaire. Data analysis used linear regression analysis. Based on the results of the study, it can be concluded that Quality of Work Life has a positive effect on job satisfaction of the Semarang City Education Office employees. Competence has a positive effect on job satisfaction of Semarang City Education Office employees. Quality of Work Life has a negative effect on the Career Plateau of Semarang City Education Office employees. Competence has a negative effect on the Career Plateau of Semarang City Education Office employees. Job satisfaction has a negative effect on the Career Plateau of Semarang City Education Office employees. Job satisfaction mediates the effect of Quality of Work Life on career plateau. Job satisfaction does not mediate the effect of competence on career plateau. Keywords: Quality of Work Life, competence, job satisfaction and career plateau Abstrak Populasi dalam penelitian ini Pegawai Dinas Pendidikan Kota Semarang yang berjumlah 95 Pegawai Negeri Sipil (PNS). Sampel dalam penelitian ini adalah Pegawai Dinas Pendidikan Kota Semarang. Pengambilan sampel dengan teknik sensus sampling sejumlah 95 pegawai. Metode pengumpulan data menggunakan kuesioner. Analisis data menggunakan analisis regresi linier. Berdasarkan hasil penelitian dapat disimpulkan Quality Of Work Life berpengaruh positif terhadap terhadap kepuasan kerja pegawai Dinas Pendidikan Kota Semarang. Kompetensi berpengaruh positif terhadap terhadap kepuasan kerja pegawai Dinas Pendidikan Kota Semarang. Quality Of Work Life berpengaruh negatif terhadap terhadap Career Plateau pegawai Dinas Pendidikan Kota Semarang. Kompetensi berpengaruh negatif terhadap terhadap Career Plateau pegawai Dinas Pendidikan Kota Semarang. Kepuasan kerja berpengaruh negatif terhadap terhadap Career Plateau pegawai Dinas Pendidikan Kota Semarang. Kepuasan kerja memediasi pengaruh antara Quality of Work Life terhadap career plateau. Kepuasan kerja tidak memediasi pengaruh antara kompetensi terhadap career plateau. Kata kunci : Quality Of Work Life, kompetensi, kepuasan kerja dan career plateau.